2021
DOI: 10.1002/rmb2.12431
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological evaluation of cesarean scar defect in women with cesarean scar syndrome

Abstract: Purpose To explore the histopathological findings of cesarean scar defect (CSD) and the immunological component in women with cesarean scar syndrome (CSS). Methods This retrospective study was conducted in a university hospital and a public hospital. A total of 63 patients with secondary infertility due to CSS who underwent laparoscopic resection of the CSD lesion were enrolled (CSS group), and 21 patients who underwent hysterectomy with a history of cesarean section we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 23 publications
(43 reference statements)
0
15
0
Order By: Relevance
“…Adenomyosis in CSD area was histologically detected in 21% of 38 patients with CSS (Donnez 2020). Similarly, our previous report revealed that the frequency of adenomyosis in CSD area was 43% of patients (Higuchi et al 2022); however, the area of endometriosis was not large, and it remains unclear whether small lesions can affect fertility. Iatrogenic adenomyosis under cesarean scar was reported in 28% of patients who underwent hysterectomy with a history of cesarean section (Morris 1995).…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Adenomyosis in CSD area was histologically detected in 21% of 38 patients with CSS (Donnez 2020). Similarly, our previous report revealed that the frequency of adenomyosis in CSD area was 43% of patients (Higuchi et al 2022); however, the area of endometriosis was not large, and it remains unclear whether small lesions can affect fertility. Iatrogenic adenomyosis under cesarean scar was reported in 28% of patients who underwent hysterectomy with a history of cesarean section (Morris 1995).…”
Section: Introductionmentioning
confidence: 57%
“…Our previous report also demonstrated there was chronic inflammation in CSD area, which may contribute to secondary infertility in women with CSS. (Higuchi et al 2022). However, there was a lack of evidence regarding inflammation and its Chronic inflammation in the uterine cavity is hypothesized to contribute to infertility in women with CSS, as the lower part of the uterus involved in CSD formation was connected to the uterine cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding hemorrhage from CSD, Tanimura et al also showed using hysteroscopy that hemorrhage occurs from CSD 54 . Our group studied histopathological findings of issues obtained from CSD lesions in women who underwent laparoscopic resection due to CSDi 55 . This study demonstrated that the proportion of endometrium present on the surface of CSD was lower in women with CSDi than in women with non‐CSDi (22% vs. 62%, respectively).…”
Section: Histopathology Of Csd In Women With Csdimentioning
confidence: 81%
“…The changes involved moderate to marked lymphocytic infiltration and capillary dilatation [ 16 ]. Higuchi A et al also reported that some chronic inflammatory markers, such as CD138, were observed in the CSD area [ 17 ]. These findings suggest the presence of chronic inflammation in the CSD area.…”
Section: Discussionmentioning
confidence: 99%
“…Morris et al investigated the pathological changes in the CSD area in 51 hysterectomy cases, in which patients presented moderate to marked lymphocytic infiltration [ 16 ]. A study by Higuchi A studied 63 cases of patients who underwent CSD lesion laparoscopic resection, and suggested that the expression of a chronic inflammatory marker was higher in women with a CSD [ 17 ]. These findings above suggested the presence of a chronic inflammatory marker in the CSD area.…”
Section: Introductionmentioning
confidence: 99%